Development of interference absorptive filters on In4(Se3)1-х Te3х and CdSb basic crystals - Стребежев, Володимир Вікторович; Нічий, Сергій Васильович; Юрійчук, Іван Миколайович; Стребежев, Віктор Миколайович (Eastern-European Journal of Enterprise Technologies, 2014)
Interference absorptive cutting light filters in the near and middle IR-region on the base of In4(Se3)1-хTe3х and CdSb crystals are obtained. Substrate crystals and films systems have been investigated by raster scanning microscopy, X-ray microanalysis, optical and electrophysical measurements to determine their suitability for developing effective cutting filters. The optical properties of defects in the crystals and substrates, their influence on the characteristics of the optical filter are studied. Low density of defect is observed in In4(Se3)1-xTe3x crystals with [010] growth direction, which is prevailing for the manufacture of optical substrates. It is found that transparency of CdSb and ZnSb crystals and substrates is kept on cooling up to 77 K. The materials for film interference systems of filters different constructions and working range are chosen. Ge-SiO semiconductors are used as a film-forming material for the filters with cutoff in the middle infrared region and Te-SrF2 in the more far regions. Ontained filters are characterized by the following parameters: cutoff slope k≥0,9, mean passband Тm≥80 %, maximum transmission Тmax≥90 %. Spectral transmission characteristics of optical filters of various designs are measured, the condition of their mechanical stability and reproducibility of optical parameters are investigated.